Rantai Pasok Pemetaan obyek destinasi wisata di kabupaten tasikmalaya menggunakan network analisis dan geographic information system - -, Miftah Fauzi; Teri Aripin, Wahyu (Jurnal Industrial Galuh, 2025)
Tasikmalaya Regency possesses a wide range of tourism potential, including natural,cultural, and religious attractions. However, the lack of optimized spatial information regarding thelocation and accessibility of tourist destinations poses a challenge in the development of the localtourism sector. This study aims to map tourism destinations and analyze optimal access routes byutilizing Geographic Information System (GIS) technology and Network Analysis features. Themethodology includes the collection of spatial and non-spatial data from 60 tourism points, hotels,and souvenir shops, map digitization using ArcGIS, and network analysis to determine optimalroutes. The analysis reveals that the distribution of tourist destinations and supporting facilities is stilluneven, with a concentration in a few main areas, while some locations remain inaccessible byadequate transportation. Route visualizations are categorized by short, medium, and long distancesand presented in the form of interactive thematic maps. The final result a map of tourism distributionand accessibility, can be utilized by the government, tourists, and tourism industry stakeholders asa reference for planning and developing integrated and sustainable tourism infrastructure.